The Effectiveness of Virtual Learning Process on Environmental Chemistry Laboratory Course - Lutfia Isna Ardhayanti; Adelia Anju Asmara; Noviani Ima Wantoputri; Elita Nurfitriyani Sulistyo; Nelly Marlina (Universitas Islam Indonesia, 2022)
The impact of advanced technology is perceived in every sector, including education. As the Ministry of Education and Culture program, distance learning has become applied in Indonesia, especially with this pandemic COVID-19. The learning model used in the course will affect student understanding in this situation, especially for an experimental study that aims to enhance student skills in the laboratory. The virtual laboratory practice is an additional learning model used in Environmental Chemistry Laboratory Course. Before, the Environmental Laboratory Course used only video to deliver learning materials. This research is experimental research that aims to evaluate the additional virtual laboratory practice's impact on student grades compared to the previous method. The research result was obtained by comparing the practical course's assessment results in 2019/2020 to 2020/2021. A questionnaire was also used to collect student opinions about the new learning method. The number of samples in this research was 395 students. The results show that the average students' grades using explanatory video only is 89, then with additional virtual laboratory practice are 88. From the questionnaire, 46% of the respondent said the application increased their understanding of the learning materials, and they also enjoyed using the application. It could be concluded that the virtual laboratory practice did not improve the assessment result of the course but enhanced the student interest. Keywords: Distance learning, Laboratory course, virtual laboratory practice